The Effect of Fulvic Acid on Alzheimer's Disease - A Systematic Review - Kaźmierkiewicz, Kornelia; Chojnacka, Martyna; Lis, Marta Ewelina; Ciechańska, Ewa; Kapuśniak, Kornel; Suszczyńska, Weronika; Rumianek-Fidziukiewicz, Katarzyna; Lasota, Zuzanna (Quality in Sport, 2025)
Introduction and aim of the study: Neurodegenerative diseases, including Alzheimer's disease, represent a significant health challenge. Therapies are being sought that could delay the development of these diseases and also mitigate their course. Fulvic acid, which is an organic humic compound with antioxidant and anti-inflammatory properties, has attracted increasing interest in the context of treating neurodegenerative diseases. Our study aims to evaluate the effects of fulvic acid on neurodegenerative diseases, mainly Alzheimer's disease, and to determine its therapeutic potential. Materials and methods: The paper is based on an analysis of studies available in databases such as PubMed, Google Scholar, ResearchGate, and other scientific databases. Clinical trials, preclinical studies, and review papers on the use of fulvic acid in the context of Alzheimer's disease were searched. Conclusions: Fulvic acid, due to its anti-inflammatory and neuroprotective abilities, shows promising potential in the treatment of Alzheimer's disease, especially in terms of slowing down the loss of cognitive function and protecting against neurodegeneration. It is advisable to conduct further studies aimed at a more thorough evaluation of the efficacy and safety of fulvic acid in the context of the treatment of Alzheimer's disease and other neurodegenerative diseases.